Structural analysis of Kirthar Fold Belt, Lower Indus Basin, Balochistan, Pakistan; implications from compression and inversion tectonics - Khalid, Adnan; Ahmad, Sajjad; Ali, Asghar; Rehman, Gohar; Yaseen, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current research work mainly focuses on tectonic evolution of the Central Kirthar Fold Belt. It also deals with the structural impact of the Late Cretaceous/Paleocene, Indian-Eurasian collision on the Central Kirthar Fold Belt which is situated in the western shear zone of Indian Plate. The Kirthar Fold Belt is different from the rest of western shear zone because it is mainly deformed by compressional tectonics which has created wide anticlines, narrow synclines and overturned folds as shown by geological mapping. It has been observed that thin-skinned deformation has played a major role in structural disharmony which is mainly seen in the Early Eocene Ghazij and Oligocene Nari formations. Seismic data shows thick-skinned deformation because the faults seem to penetrate deeper stratigraphic levels. Involvement of the basal decollement and the penetration of the interpreted faults to the level of basement rocks is also evident from the exposure of Jurassic/Cretaceous rocks at surface on the western part of the mapped area. Cross sections data shows that Kirthar Thrust Fault has a structural throw around 3-4 km in the Kirthar Folded Zone featuring deformational front while the seismic data and well data shows that this intensity decreases in the Kirthar Foredeep Zone towards east where the structural throw is about 2-3 km. Restoration of cross sections show an overall 17.3% shortening which shows that the area is under influence of compressional stresses.